Analysis of loaded characteristics of helical curve face gear. (September 2017) - He, Chunjiang; Lin, Chao
Highlights: The meshing equations for non-circular gear contacting with helical curve face gear without misalignment. The contact path and functions of transmission errors with different alignment errors are proposed. The principal curvatures, contact area and contact stress on every tooth and the half cycle of helical curve face gear have been established separately. Abstract: As a new gear pair, the helical curve face gear pair have not been widely applied as normal face gear. It can be used to substitute crank-slider mechanism to achieve variable transmission ratio and improve the structure and characteristics to some extent, such as grinders, planers and so on. The mathematical model of the helical curve face gear pair and the tooth contact analysis are necessary for the theoretical analysis of this gear pair. Based on the theory of gear meshing and coordinate transmission, the meshing equations for non-circular gear contacting with helical curve face gear without misalignment are obtained. On the basis of Hertz's theory, the principal curvatures at contact point are represented. And the contact area on every tooth and the half cycle of helical curve face gear have been established separately. As well as the contact stress on every tooth and half cycle of helical curve face gear. However, there may be misalignment during the meshing of this gear pair, this paper also covers the contact path and the functions of transmission errors with misalignment, includes the comparison of helical curve face gear and straight curve face gear. The developed theories for complex tooth surface are verified by experiment. These analysis show the contact characteristics of this gear pair during the meshing process and provide the theoretical support for further analysis and application of helical curve face gear pair.